Monthly anomalies of sea surface chlorophyll-a concentration in the Khanh Hoa waters of Vietnam related to ENSO phenomenon - Vu, Van Tac (Vietnam Journal of Marine Science and Technology, 2021)
Based on the monthly averaged sea surface chlorophyll-a concentration data continuously for more than 17 years (Jul. 2002–Dec. 2019), the analyzed results show that the averaged chlorophyll-a concentration in Khanh Hoa waters was 0.58 mg/m3, and the monthly average variation was ± 0.14 mg/m3 (that is equivalent to about ± 24%). Under the impact of ENSO phenomena, in the years when the double La Niña events occurred (two consecutive years in the La Nina event occurs), the chlorophyll-a anomaly index fluctuated from -0.99 mg/m3 to 1.62 mg/m3. These are very strong fluctuation levels, corresponding to the decrease or increase in chlorophyll-a concentration from 86% to 279%. In the El Niño years, the fluctuations of chlorophyll-a concentration were little affected unless the two previous years in which the double La Niña event occurred. These fluctuations have significantly impact nutritional resources and water quality because chlorophyll-a concentration is one of the key indices in studying the health status of any natural marine ecosystem. In addition, chlorophyll-a concentration in Khanh Hoa waters often varies between seasons. The averaged chlorophyll-a concentration reaches its maximum value in the winter, then decreases gradually in the spring and usually reaches the minimum value in the summer, then rises gradually again in the autumn.